PENGARUH LIKUIDITAS, STRUKTUR MODAL, PERPUTARAN KAS, DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PERUSAHAAN - Yesika Ade Noviyani; Hesty Ervianni Zulaecha; Imam Hidayat; Ahmad Jayanih (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2022)
Profitability shows the company's ability to earn profits related to sales, total assets and capital with certain measurements. The purpose of this study was to determine the effect of liquidity, capital structure and cash turnover on the profitability of empirical study companies in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2015 - 2021 period. The research approach used is quantitative research. The research period was carried outfor 7 years, namely the 2015 - 2021 period. The population of this study included all food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2015 - 2021 period. The sampling technique was using purposive sampling technique. Based on the established criteria, 10 companies have met these criteria. The type ofdata used is secondary data obtained from the official website of the Indonesia Stock Exchange. The analysis method used is panel data regression analysis using Eviews software version 10.0. In this study, profitability is measured using return on assets. The results showed that liquidity as measured by the current ratio had a positive effect on profitability, while the capital structure as measured by the debt to equity ratio had negative effect on profitability, cash turnover had no negative effect on profitability as well as sales growth as measure by the degree of operating leverage had a negatif effect on profitablity. The simultaneous test results for liquidity, capital structure and cash turnover have ajoint effect on profitability.